Truncated PPM1D impairs stem cell response to genotoxic stress and promotes growth of APC-deficient tumors in the mouse colon - Burocziova, Monika; Burdova, Kamila; Martinikova, Andra S.; Kasparek, Petr; Kleiblova, Petra; Danielsen, Stine A.; Borecka, Marianna; Jenikova, Gabriela; Janečková, Lucie; Pavel, Jozef; Zemankova, Petra; Schneiderova, Michaela; et al. (Cell death & disease, 2019)
Protein phosphatase magnesium-dependent 1 delta (PPM1D) terminates cell response to genotoxic stress by negatively regulating the tumor suppressor p53 and other targets at chromatin. Mutations in the exon 6 of the PPM1D result in production of a highly stable, C-terminally truncated PPM1D. These gain-of-function PPM1D mutations are present in various human cancers but their role in tumorigenesis remains unresolved. Here we show that truncated PPM1D impairs activation of the cell cycle checkpoints in human non-transformed RPE cells and allows proliferation in the presence of DNA damage. Next, we developed a mouse model by introducing a truncating mutation in the PPM1D locus and tested contribution of the oncogenic PPM1D T allele to colon tumorigenesis. We found that p53 pathway was suppressed in colon stem cells harboring PPM1D T resulting in proliferation advantage under genotoxic stress condition. In addition, truncated PPM1D promoted tumor growth in the colon in Apc min mice and diminished survival. Moreover, tumor organoids derived from colon of the Apc min Ppm1d T/+ mice were less sensitive to 5-fluorouracil when compared to Apc min Ppm1d +/+ and the sensitivity to 5-fluorouracil was restored by inhibition of PPM1D. Finally, we screened colorectal cancer patients and identified recurrent somatic PPM1D mutations in a fraction of colon adenocarcinomas that are p53 proficient and show defects in mismatch DNA repair. In summary, we provide the first in vivo evidence that truncated PPM1D can promote tumor growth and modulate sensitivity to chemotherapy.